(3ef CSQGQ GdJYHjQ GdbQBfj (B:s (3OQGSI JMdjdjI dShQI GdCMRGH (B/s - (3CHh ehSi, eMeO eMeO MSfjfs 1937- ((3GdbGgQI (B- (3eUQ (B:s (3ecJHI hgHI ,s, 1996)
(3YfjJ gPg GdOQGSI HGdeaQOGJ GdbQBfjI, ahVMJ eYGfjgG GddZhjI heSJ CUhdgG GdGTJbGbjI, Ke QOOJgG aj GdYHGQGJ GdHdjZI GdJj JMed QjM GdHGOjI hCUGdI fMjRJgG, eYJbOI Cf Pdc ef CLd GdYhGFO aj GdJQHjI GddZhjI, Ke hbaJ YfO UhQ GdJQGcjH hCTGQJ Edi CSQGQ GdHdGZI ajgG eMGaXI Ydi ObI GdeaGgje GdYdejI aj HjGf gPg GdCSQGQ dJchf gPg GdUjGZGJ eGOI COHjI jYjgG GdWdGH hYjG MSfG aJfaK aj bdhHge CSQGQ GdaUGMI hJcTa ajgG Yf efGHY hMj GdLeGd, hJbje GdedcGJ Ydi efgGL GdSdjbI GdYQHjI GdNGdUI ajgjFhf HPdc Edi Jdbj CNPI GdEYLGR aj GdLedI GdbQBfjI(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdbQBfs -- (3HdGZIs; (3GdbQBfs -- (3HdGZIs